Enhancing Youth Crime Prevention in Albania through Integrated Education and Sport Policies - Gashi, Ada; Myftaraj, Ervin; Sotirofski, Kseanela (European Journal of Social Science Education and Research, 2025)
Youth crime prevention increasingly relies on coordinated education and sport policies that create protective environments for adolescents. This study examines how these two policy domains can jointly reduce youth offending in Albania, where, according to the Criminal Code of the Republic of Albania, the minimum age of criminal responsibility begins at 14. Grounded in criminological theories of social control and routine activity, combined with positive youth development and sport-for-development perspectives, the research develops an integrated framework for sport-based prevention initiatives (SBPIs) within educational and community systems. Using official data from the Albanian Institute of Statistics (INSTAT) for 2022–2024, Albanian Football Association (FSHF), Ministry of Education and Sport and findings from a 2025 parental questionnaire conducted with 50 respondents, the study triangulates national trends with family level attitudes toward adolescent sport participation. Results reveal a gradual increase in under-18 suspected offenders 1,773 in 2022, 2,005 in 2023, and approximately 1,803 (4.5% of 40,057 total suspects) in 2024 while survey data indicate strong parental support for sport as a means of reducing screen dependency and improving socialization and health. The findings align intervention priorities with empirically supported risk and protective factors, emphasizing structured after-school sport programs, mentoring, safeguarding, and inter-ministerial coordination. While SBPIs can enhance inclusion and resilience, causal links to crime reduction remain complex and context dependent. The study concludes with an evidence-based roadmap for implementing education and sport driven prevention strategies to strengthen Albania’s adolescent support systems.